THE APPLICABILITY OF LEGAL RULES ON FICTITIOUS NEGATIVE DECISIONS AND FICTITIOUS POSITIVE DECISIONS - Jenrison Nainggolan; Aan Eko Widiarto; Sudarsono (CV. RADJA PUBLIKA, 2025)
The objective of this study is to examine the legal validity of Negative and Positive Fictitious Decisions from the perspective of state administrative law. This study uses normative legal research methods by analyzing variety of literature. The research methods is based on legislationand uses secondary data consistin primary legal materials, secondary legal materials, presented in a wualitative descriptive manner. The findings indicate that the authority of the PTUN to Adjudging disputes of positive fictitious disputes has been removed in the provisions of Article 175 of the Job Creation Law and the provisions for derogation (revocation) of the provisions of Article 3 of the Peratun Law are not regulated in the State Administration Law and the Job Creation Law, so the principle of preference lex posteriori derogat lex priori is no longer appropriate to use. Additionally, the PTUN authority standards that attempt both positive and negative fake disagreements are no longer in conflict. Since the PTUN still has the authority to attempt Negative Fictitious, Positive Fictitious essentially has the executive's complete authority. Therefore, one example of a legal safeguard for citizens against false judgments made by government officials is the requirements of Article 3 of the Peratun Law.